Pelatihan Menulis Karya Ilmiah Berbasis Systematic Literature Review (SLR) Untuk Meningkatkan Publikasi Mahasiswa STMIK Kreatindo Manokwari - Juni Syaputra; Elvi Rahmi; Risma Petrus (CV. Multi Kreasi Media, 2026)
This community service activity was conducted to increase the productivity of student publications through training and mentoring in compiling scientific papers based on Systematic Literature Review (SLR). The main challenges faced by students are their low ability to write systematic scientific articles and their lack of experience in scientific publications. The implementation stages of the activity consist of preparation, training, intensive mentoring, and evaluation. Training will be provided focused on the structure of scientific articles, strategies for finding reputable scientific literature sources, and the application of the SLR method. Mentoring is carried out continuously until students produce a draft of a scientific article. The results of the PKM activity show a significant increase in students' understanding and skills in producing scientific papers as seen from the increase in post-test scores by 35% compared to the pre-test score. In addition, 30% of them are ready to be submitted to national journals. This activity has made a very positive contribution to improving academic culture and student readiness in scientific publication.